2020
DOI: 10.1002/jmri.27197
|View full text |Cite
|
Sign up to set email alerts
|

MRI‐Based Radiomics Models Developed With Features of the Whole Liver and Right Liver Lobe: Assessment of Hepatic Inflammatory Activity in Chronic Hepatic Disease

Abstract: Background: The noninvasive assessment of hepatic inflammatory activity (HIA) is crucial for making clinical decisions and monitoring therapeutic efficacy in chronic liver disease (CLD). Purpose: To develop MRI-based radiomics models by extracting features from the whole liver and localized regions of the right liver lobe, compare the efficiency of two radiomics models, and further develop a radiomics nomogram for the assessment of HIA in CLD. Study Type: Retrospective. Population: In all, 137 consecutive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 31 publications
(60 reference statements)
0
10
0
Order By: Relevance
“…However, it should be noted that the specialized software of LiverMultiScan TM limits its widespread use, because of necessary payment for this software. Recently, in a small study of 137 Chinese patients with chronic hepatitis B or other chronic liver diseases, the authors found that MRI-based radiomics models yielded good diagnostic performance for identifying hepatic inflammation (24). However, as this study was limited to a single center without any independent external validation, the robustness and generalizability of the findings remain unconfirmed.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…However, it should be noted that the specialized software of LiverMultiScan TM limits its widespread use, because of necessary payment for this software. Recently, in a small study of 137 Chinese patients with chronic hepatitis B or other chronic liver diseases, the authors found that MRI-based radiomics models yielded good diagnostic performance for identifying hepatic inflammation (24). However, as this study was limited to a single center without any independent external validation, the robustness and generalizability of the findings remain unconfirmed.…”
Section: Discussionmentioning
confidence: 88%
“…Regarding imaging techniques used for assessing hepatic inflammation, the visual examination of imaging modalities has been used to determine hepatic inflammatory activity in the past (34). However, the high inter-observer variability and the unsatisfactory performance largely limit its use in clinical practice (24). França et al (17) recently proposed a quantitative method of 'intra-voxel incoherent motion diffusion-weighted MRI' for the assessment of hepatic inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…108,109 Some reports used T1 mapping and T2 mapping to assess inflammation and have found some correlation, while others have reported that radiomic models based on T1 values corrected for T2* or T2 weighted sequences have shown promising results. [110][111][112]…”
Section: Quantitative Mri Of Livermentioning
confidence: 99%